Gambaran kolesterol total pada lansia di Puskesmas I Denpasar Selatan - I Gusti Agung Ayu Putu Swastini (Meditory : The Journal of Medical Laboratory, 2021)
background Total Cholesterol is the amount of cholesterol carried In all cholesterol carrying particle In the blood including HDL, LDL, and VLDL. THR elderly will experience the aging process and decreased physiology function change which can lead tO reduced activity of the receptors of controlling the amount of choledterol In the body. The normal value of total cholesterol level is normal 200 mg/dl, high limit 200-239 mg/dl, and high 240 mg/dl. Risk factors can affect total cholesterol level are age gender, BMI, and blood pressure. The purpose of this study was tO determine to description of total cholesterol levels In elderly. The research method uses discritive research with purpisive sampling method involving 115 respondents take using secondary data for the elderly at Puskesmas I South Denpasar. THR results showed That most elderly respondents who experienced an increase total cholesterol were female as many as 26 people (22,6%) the age group 65-74 years as many as 18 people (15,7%), In the normal BMI category as many as 26 people (22,6%), and normal bolos pressure as many as 25 people (21,7%), high limit total cholesterol levels as many 45 people(31,9%), and high total cholesterol levels as many as 45 people (31,9%).